2016
DOI: 10.1016/s0140-6736(15)00448-1
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after thrombus aspiration for ST elevation myocardial infarction: 1-year follow-up of the prospective randomised TOTAL trial

Abstract: SummaryBackground-Two large trials have reported contradictory results at 1 year after thrombus aspiration in ST elevation myocardial infarction (STEMI). In a 1-year follow-up of the largest randomised trial of thrombus aspiration, we aimed to clarify the longer-term benefits, to help guide clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
131
1
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(142 citation statements)
references
References 28 publications
(25 reference statements)
4
131
1
5
Order By: Relevance
“…Mechanistically, the postulated benefits of aspiration thrombectomy were less distal embolization and prevention of reperfusion injury. However, the large randomized TOTAL trial did not show any benefit for use of routine thrombectomy, and of concern there was a signal for harm with increased risk of stroke in the thrombectomy arm of the study [39][40][41]. The mechanism of stroke is likely due to aspiration back of clot and subsequent embolization to the brain.…”
Section: Thrombectomy Systemsmentioning
confidence: 99%
“…Mechanistically, the postulated benefits of aspiration thrombectomy were less distal embolization and prevention of reperfusion injury. However, the large randomized TOTAL trial did not show any benefit for use of routine thrombectomy, and of concern there was a signal for harm with increased risk of stroke in the thrombectomy arm of the study [39][40][41]. The mechanism of stroke is likely due to aspiration back of clot and subsequent embolization to the brain.…”
Section: Thrombectomy Systemsmentioning
confidence: 99%
“…Nevertheless, two recent trials, the Thrombus Aspiration in ST-Elevation Myocardial Infarction in Scandinavia (TASTE) trial and the 'The Trial of Routine Aspiration Thrombectomy with PCI versus PCI Alone in Patients with STEMI (TOTAL)' [41][42][43][44], showed no benefits in terms of clinical outcomes of thrombus aspiration during primary PCI, despite manual thrombectomy was associated to an improvement of ST resolution and a reduced distal embolization [41][42][43][44]. As consequence of this large randomized trial, ACC/AHA/SCAI guidelines reported that the 'usefulness of selective and bailout aspiration thrombectomy in patients undergoing primary PCI is not well established (Class II; level of evidence B)' and the routine use of manual aspiration during primary PCI is not useful (Class III; level of evidence A) [2].…”
Section: Manual Thrombectomymentioning
confidence: 99%
“…Accordingly, careful thromboaspiration was advocated to optimize acute procedural results and to prevent the occurrence of late acquired malapposition resulting from the disappearance of the residual thrombus entrapped behind the stent (1,2). However, the widespread systematic utilization of manual thrombus aspiration during routine primary angioplasty procedures has been recently halted in the light of the negative results of 2 large controlled trials of routine thromboaspiration in STEMI powered for major clinical events (1,3). Moreover, the delayed healing and the potential toxic effects on the vessel wall leading to positive remodeling and late acquired malapposition occasionally Perspective Bioresorbable vascular scaffolds in patients with acute myocardial infarction: a new step forward to optimized reperfusion?…”
Section: Introductionmentioning
confidence: 99%